The effect of building height diversity on outdoor microclimate conditions in hot climate. A case study of Dubai-UAE - Shareef, Sundus (2020)
Urban geometry and buildings' morphology affect the thermal behaviour of the spatial en vironment. Urban compactness is a key variable that affects thermal performance in hot climates. Previous studies focused on traditional methods of increasing the shading effect, e.g. buildings' height/canyon width (H/W) ratio. This research looks at alternative methods to increase the shading effect by changing the block's orientation and buildings' height diversity within the urban block. ENVI-Met 4.1 software is used to predict the outdoor thermal performance of a base case urban configuration then used to evaluate several proposed urban configurations and compare their thermal performance to the base case configuration. Orientation was the most influential factor in the outdoor air. For the base case, a reduction of 1.8 °C degree was noted between the N-S and NE-SW orientations. An urban configuration with significant variation in the buildings' height resulted in more reduction in outdoor air temperature compared to a config uration with gradual variation in the buildings' heights. Orienting the significant variation in buildings' heights along the short axis of the urban block resulted in a reduction of the air temperature in NW-SE orientation by 1.1 °C.